Pembelajaran Sastra Berbasis Karakter l - Devi Intan Sari Sagala; Wildani Akhiriani; Mazidatul Adawiyah Nasution (Universitas Dehasen Bengkulu, 2022)
Literature in character education is in accordance with the expectations of the 2013 curriculum, which prioritizes aspects of attitude in the formation of student character. Understanding literary works can start with the intrinsic aspects contained in them such as setting, characters, plot, point of view, themes and so on. Character values are contained in character-based literary works, so there needs to be an understanding of the meaning of literary works that contain various character values so that they need to be applied in the attitudes of students through their environment. Character-based literary learning is more directed at understanding literary works that have character values so that they can contribute to the formation of students' character. This research uses a literature review method, using librarian study techniques and literature studies, namely data collection techniques by reviewing books/journals, reading, literature, notes and various reports related to the problem to be solved.